Precision medicine in the diagnosis and treatment of male lower urinary tract symptoms suggestive of benign prostatic hyperplasia - Jing-Liang Chen; Yuan-Hong Jiang; Cheng-Ling Lee; Hann-Chorng Kuo (Tzu Chi Medical Journal)
Male lower urinary tract symptoms (LUTSs) are highly prevalent in men and the incidence increases with aging. The pathophysiology of male LUTSs might be bladder outlet dysfunctions such as bladder neck (BN) dysfunction, benign prostatic obstruction, and poor relaxation of external sphincter and bladder dysfunctions such as detrusor overactivity (DO), detrusor underactivity, DO, and inadequate contractility. Male LUTSs include voiding and storage symptoms, and precision diagnosis should not be done based on the symptoms alone. Videourodynamic study provides a thorough look at the bladder and bladder outlet and can clearly demonstrate the underlying pathophysiology when the initial medication fails to relieve LUTS. Medical treatment should be given based on the underlying pathophysiology of LUTS, and surgical intervention to remove prostate should only be performed when a definite bladder outlet obstruction due to prostatic obstruction has been confirmed by invasive urodynamic study.